Corporate characteristics and anthropological disasters - Radu Ionescu (GeoPatterns, 2016)
Critical infrastructure is business. All critical infrastructure is managed by companies, whether state, public, or joint companies. These companies have owners (stockholders), again private and/or state entities, and employees (managers and workers). If we are to understand how an operationalisable behaviour such as whistleblowing works in relation to critical infrastructure vulnerability we must first analyse the wider level relationship companies/corporations have with society, particularly in terms of human health and safety and the environment. We therefore look at corporate accidents, characteristics, dangers, and accountability. The aim is to offer a background on which we can identify what makes a company behave ethically.